2015
DOI: 10.1016/j.bbacli.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to study oxidative stress in neonatal respiratory distress syndrome

Abstract: BackgroundRespiratory distress syndrome of the neonate (neonatal RDS) is still an important problem in treatment of preterm infants. It is accompanied by inflammatory processes with free radical generation and oxidative stress. The aim of study was to determine the role of oxidative stress in the development of neonatal RDS.MethodsMarkers of oxidative stress and antioxidant activity in umbilical cord blood were studied in infants with neonatal respiratory distress syndrome with reference to healthy newborns.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
(30 reference statements)
5
32
1
Order By: Relevance
“…4 ROS can cause damage to a variety of cellular molecules, including lipids, proteins, and DNA, which results in cell injury and may induce respiratory cell death. 5,6 ROS also interact with pulmonary surfactant, thus delaying the normal functioning of the lung. 5 This process can contribute to the pathogenesis of RDS and very likely leads to severe RDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 ROS can cause damage to a variety of cellular molecules, including lipids, proteins, and DNA, which results in cell injury and may induce respiratory cell death. 5,6 ROS also interact with pulmonary surfactant, thus delaying the normal functioning of the lung. 5 This process can contribute to the pathogenesis of RDS and very likely leads to severe RDS.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 ROS also interact with pulmonary surfactant, thus delaying the normal functioning of the lung. 5 This process can contribute to the pathogenesis of RDS and very likely leads to severe RDS. 7 ROS have been implicated in the molecular damage seen in the bronchoalveolar lavage (BAL) fluid of patients with RDS.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that the association of melatonin with misoprostol, a gastric mucosal protective agent, is more beneficial than melatonin therapy alone. These studies on animals found that the administration of 10 mg/kg body weight melatonin for 3 days to animals with induced NEC-like lesions significantly reduced the severity of the disease by decreasing cytokine levels and stimulating antioxidant enzyme activity [45,48].…”
Section: Effects Of Oxidative Stress In Ulceronecrotic Enterocolitismentioning
confidence: 99%
“…Caspase 6 and, subsequently, caspase 3 are activated. NMDA receptor activation depresses the mitochondrial respiratory process and induces apoptosis-a process which is not found in adults, known as the NMDA paradox [41,48].…”
Section: Effects Of Oxidative Stress In Neonatal Asphyxia and Hypoxicmentioning
confidence: 99%
“…Elevations of urinary leukotriene E 4 have been associated with ARDS in adults ( 173 ) and development of BPD in infants ( 174 , 175 ), though variations observed may be highly affected by gestational age and maturity ( 176 ). Several studies of neonates have demonstrated alterations in the levels of markers of oxidative stress and DNA damage in RDS ( 175 , 177 ), and one study of BAL fluid in children with ALI found alterations in the concentrations of multiple cell surface lipids indicative of alveolar–capillary membrane damage ( 21 ). Eicosanoids and other lipid-derived and small molecules may serve as useful biomarkers, especially of vascular physiology, oxidative damage, and inflammation, in future studies of children with ARDS.…”
Section: Biomarker Subgroupsmentioning
confidence: 99%